2023
DOI: 10.1186/s13041-022-00991-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pain processing in the primary somatosensory cortex and anterior cingulate cortex

Abstract: Pain is known to have sensory and affective components. The sensory pain component is encoded by neurons in the primary somatosensory cortex (S1), whereas the emotional or affective pain experience is in large part processed by neural activities in the anterior cingulate cortex (ACC). The timing of how a mechanical or thermal noxious stimulus triggers activation of peripheral pain fibers is well-known. However, the temporal processing of nociceptive inputs in the cortex remains little studied. Here, we took tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In addition, theta rhythmicity can also reflect a brain state of social response to social and fearful stimuli, further contributing to the pain experience (Tendler and Wagner, 2015). Meanwhile, changes in amplitudes of gamma oscillations have been shown to correlate with both evoked stimulus intensity and subjective pain rating in several studies (Gross et al, 2007;Michels et al, 2011;Zhang et al, 2012;Schulz et al, 2015;Mouraux and Iannetti, 2018;, Frontiers in Neuroscience 08 frontiersin.org 2019; Vanneste and De Ridder, 2021), where recent animal studies have also shown that theta and gamma oscillations in the ACC and S1 may encode the intensity of pain (Harris-Bozer and Tan et al, 2019;Sun et al, 2022Sun et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, theta rhythmicity can also reflect a brain state of social response to social and fearful stimuli, further contributing to the pain experience (Tendler and Wagner, 2015). Meanwhile, changes in amplitudes of gamma oscillations have been shown to correlate with both evoked stimulus intensity and subjective pain rating in several studies (Gross et al, 2007;Michels et al, 2011;Zhang et al, 2012;Schulz et al, 2015;Mouraux and Iannetti, 2018;, Frontiers in Neuroscience 08 frontiersin.org 2019; Vanneste and De Ridder, 2021), where recent animal studies have also shown that theta and gamma oscillations in the ACC and S1 may encode the intensity of pain (Harris-Bozer and Tan et al, 2019;Sun et al, 2022Sun et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Previous neuroimaging studies based on functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) have revealed that chronic pain causes maladaptive changes in a distributed cortical network including the primary somatosensory cortex (S1), the anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (dlPFC), and the insular cortex (IC; Apkarian et al, 2004Apkarian et al, , 2005Brooks and Tracey, 2005;Tracey, 2005;Tracey and Mantyh, 2007;Mouraux and Iannetti, 2018;Prichep et al, 2018;Van Der Miesen et al, 2019;. These findings are further supported by studies in animal models (Bingel and Tracey, 2008;Xiao et al, 2019;Sun et al, 2023). Less is known, however, about how the brain, in particular the cortex, dynamically responds to a temporally regulated stimulus Sun et al, 2021).…”
Section: Ethics Statementmentioning
confidence: 90%
“…In addition, theta rhythmicity can also reflect a brain state of social response to social and fearful stimuli, further contributing to the pain experience (Tendler and Wagner, 2015). Meanwhile, changes in amplitudes of gamma oscillations have been shown to correlate with both evoked stimulus intensity and subjective pain rating in several studies (Gross et al, 2007;Michels et al, 2011;Zhang et al, 2012;Schulz et al, 2015;Mouraux and Iannetti, 2018;Zhou R. et al, 2018;Dinh et al, 2019;May et al, Frontiers in Neuroscience 08 frontiersin.org 2019; Baroni et al, 2020;Vanneste and De Ridder, 2021), where recent animal studies have also shown that theta and gamma oscillations in the ACC and S1 may encode the intensity of pain (Harris-Bozer and Peng, 2016;Tan et al, 2019;Sun et al, 2022Sun et al, , 2023Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous neuroimaging studies based on functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) have revealed that chronic pain causes maladaptive changes in a distributed cortical network including the primary somatosensory cortex (S1), the anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (dlPFC), and the insular cortex (IC; Apkarian et al, 2004Apkarian et al, , 2005Brooks and Tracey, 2005;Tracey, 2005;Tracey and Mantyh, 2007;Kucyi and Davis, 2015;Mouraux and Iannetti, 2018;Prichep et al, 2018;Van Der Miesen et al, 2019;Chen, 2021). These findings are further supported by studies in animal models (Bingel and Tracey, 2008;Zhang et al, 2017;Xiao et al, 2019;Sun et al, 2023). Less is known, however, about how the brain, in particular the cortex, dynamically responds to a temporally regulated stimulus (Wager et al, 2013;Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…The brain network of the self-pain experience is governed by the two dominant processes mentioned above (Frediani & Bussone, 2019;Melzack, 1999): emotional, i.e., affective-motivational (e.g., anterior cingulate cortex, amygdala, anterior insula, and prefrontal cortex, Xiao & Zhang, 2018); and cognitive, i.e., cognitive evaluation (e.g., anterior cingulate cortex, prefrontal cortex, medial and posterior cingulate cortex, Kong et al, 2006). Moreover, during first-hand pain experience, regions associated with sensory processing are activated, such as the somatosensory cortex SI and SII responsible for detecting the location and intensity of pain (e.g., Sun et al, 2023;Vierck et al, 2013). However, certain researchers also observed activations of these sensory-related regions during the process of empathy (e.g., Bufalari et al, 2007;Cheng et al, 2008).…”
mentioning
confidence: 99%